2011
DOI: 10.1111/j.1750-3841.2011.02279.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extrusion on the Antioxidant Capacity and Color Attributes of Expanded Extrudates Prepared from Purple Potato and Yellow Pea Flour Mixes

Abstract: Foods with antioxidant capacity provide protection against cardio-vascular, certain forms of cancers, and Alzheimer's diseases caused by oxidative damages and contribute health benefits. The effect of extrusion cooking on the antioxidant capacity and color attributes of extruded products prepared from 3 selected formulations of purple potato and yellow pea flours using a co-rotating twin screw extruder were studied. Expansion ratios of the extruded products varied from 3.93 to 4.75. The total antioxidant capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 48 publications
7
66
1
2
Order By: Relevance
“…(Altan et al 2009;Sharma et al 2012). Apart from vegetable flour addition, antioxidant compounds as well as antioxidant activity change in extruded products could also be attributed to the release of phenolic compounds from cell walls (e.g., breaking complex polyphenols into low molecular weight phenolic compounds), to interaction of phenolics with protein, and to formation of Maillard reaction products as a result of high extrusion temperatures especially at higher temperatures (Nayak et al 2011;Stojceska et al 2009). The phenolic content of broccoli enriched extrudates decreased with the feed moisture content rise.…”
Section: Phenolic Content Of Extrudatesmentioning
confidence: 96%
See 1 more Smart Citation
“…(Altan et al 2009;Sharma et al 2012). Apart from vegetable flour addition, antioxidant compounds as well as antioxidant activity change in extruded products could also be attributed to the release of phenolic compounds from cell walls (e.g., breaking complex polyphenols into low molecular weight phenolic compounds), to interaction of phenolics with protein, and to formation of Maillard reaction products as a result of high extrusion temperatures especially at higher temperatures (Nayak et al 2011;Stojceska et al 2009). The phenolic content of broccoli enriched extrudates decreased with the feed moisture content rise.…”
Section: Phenolic Content Of Extrudatesmentioning
confidence: 96%
“…Brassica vegetables belong to Cruciferous family, including a number of widely consumed species such as cabbage, cauliflower, broccoli, Brussels sprouts and kale, which exhibit both antioxidant and anticarcinogenic properties (Bisharat et al 2013;Nayak et al 2011;Sarawong et al 2014;Verhoeven et al 1997). In addition to antioxidant vitamins, carotenoids, and polyphenols, Brassica vegetables provide a large group of glucosinolates, which possess rather low antioxidant activity (Plumb et al 1996), but the products of their hydrolysis can protect against cancer (Keum et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…TPC after extrusion decreased in all samples with 5-15% added BPF except TPC where it increased in the sample with 20% of carrot BPF addition. Therefore, losses in the TP content of the formulations under extrusion are expected to occur, due to break down of complex polyphenols to other phenolic or nonphenolic compounds, at a consequence of high temperature conditions (Nayak et al, 2011). Another explanation for the higher TPC after heating, for apple and pumpkin BPF addition at least in part is an increased formation of anthocyanins of browning compounds caused by the Maillard reaction at high temperatures.…”
Section: Moisture and Total Phenolic Compounds (Tpc)mentioning
confidence: 99%
“…Production of juice from apple, carrots and pumpkin result in such by-products as bark, mark, peel, seeds which are still rich in bioactive compounds (Figuerola & Mar, 2005;Nayak et al, 2011). Vegetables are one of major antioxidants sources.…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion of ABF additionally decreased the lightness of samples, colour saturation (L*) and hue did not show a clear trend. Some authors also reported a darkened colour of the extrudates due to Maillard browning during extrusion which also can cause the colour change , Nayak et al, 2011, Jain et al, 2013.…”
Section: Resultsmentioning
confidence: 99%